False alarm ebook - Heley, Veronica (Abbott Agency, 2013)
Bea finds herself obligated to help a businessman whose life is in danger . . . and is sucked into a community packed with scandal, intrigue and corruption Bea finds herself obligated to help a businessman whose life is in danger . . . and is sucked into a community packed with scandal, intrigue and corruption|Bea Abbot is asked to find the man or woman who laid a booby trap for Sir Lucas Ossett, the powerful head of an international company, in his own block of flats. She finds Sir Lucas's wife in a state of fear, while gossiping elderly ladies cast doubt on the probity of their eclectic neighbours. Soon it's clear that Sir Lucas's influence reaches out to touch and perhaps corrupt even those nearest to Bea, while trivial incidents escalate into violence – and death.